Prospective Application of Vitrificating High-Level Liquid Waste From Power Reactor Spent Fuel in Cold Crucible Induction Melter - LI Yu-song; WANG Ze-xue; ZHANG Sheng-dong; ZHU Dong-dong; HONG Ye; TAN Sheng-heng; QIE Dong-sheng; ZHANG Hua; XIAN Liang; LONG Hao-qi (He huaxue yu fangshe huaxue, 2023)
With the development of nuclear power technology in China, the need for glass vitrification of high-level liquid waste(HLLW) from a power reactor spent fuel has become more and more urgent. In this paper, the application prospect of cold crucible induction melter(CCIM) in the treatment of HLLW from a power reactor spent fuel is reviewed, and the technical advantages, design advantages and technological advantages of CCIM are described in detail. On that basis, some suggestions for the future development of CCIM are proposed.